The genome sequence of a soldier beetle, Malthinus seriepunctatus Kiesenwetter, 1851 [version 1; peer review: 2 approved] - Maxwell V. L. Barclay; Michael F. Geiser; Ryan Mitchell (Wellcome Open Research)
We present a genome assembly from a specimen of Malthinus seriepunctatus (a soldier beetle; Arthropoda; Insecta; Coleoptera; Cantharidae). The genome sequence has a total length of 338.81 megabases. Most of the assembly (99.73%) is scaffolded into 6 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 20.41 kilobases in length.